Conferencia de Noam Chomsky - Chomsky, Noam (Revista de Estudios Árabes, 2014)
The author criticizes U.S.A. support of dictatorships in the Middle East that serve American oil interests in the region. In the seventies and eighties, massive military aid was provided to Iraq in its war against Iran and the Kurds. As the invasion of Kuwait was contrary to U.S.A. interests, the first Gulf War ensued, followed by sanctions that lasted ten years, causing enormous suffering and material loss to Iraq and its people. Turkey´s devastating offensive against the Kurds was possible thanks to massive arms supplies provided by the U.S.A. Economic, political and military backing of Israel by America is unconditional, in spite of repeated U.N. Security Council Resolutions that are ignored by both countries.